2012
DOI: 10.3748/wjg.v18.i33.4517
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic hepatitis B in pregnancy

Abstract: Pregnancy associated with chronic hepatitis B (CHB) is a common and important problem with unique challenges. Pregnant women infected with CHB are different from the general population, and their special problems need to be considered: such as the effect of hepatitis B virus (HBV) infection on the mother and fetus, the effect of pregnancy on replication of the HBV, whether mothers should take HBV antiviral therapy during pregnancy, the effect of these treatments on the mother and fetus, how to carry out immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 50 publications
0
41
0
21
Order By: Relevance
“…The results of research in this area are somewhat controversial, however, most authors concluded that pregnancy does not affect the course of CHB [3,5,8,9].…”
Section: Problem Statement and Analysis Of The Recent Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of research in this area are somewhat controversial, however, most authors concluded that pregnancy does not affect the course of CHB [3,5,8,9].…”
Section: Problem Statement and Analysis Of The Recent Researchmentioning
confidence: 99%
“…According to various estimates, about 2 billion people in the world are infected with hepatitis B virus (HBV) and 300-450 million patients with chronic HBV (CHB), who are a constant source of infection [7,8,9].…”
Section: Problem Statement and Analysis Of The Recent Researchmentioning
confidence: 99%
“…52,93 Some reports support administration of HBIG to pregnant women infected with HBV in order to prevent HBV infection in the uterus. [94][95][96] In the UK, HBIG is accepted for mothers positive for hepatitis B e antigen (HBeAg) or with HBV-DNA levels above 1.0£10…”
Section: Efficacy and Safety Of Hepatitis B Immune Globulin (Hbig)mentioning
confidence: 99%
“…45 Among pregnant women, hepatitis B is a pre-existing or concurrent liver disease, 46 and the clinical symptoms in infected pregnant women are similar to those of non-pregnant women. 47,48 HBV infection does not directly threaten maternal or fetal lives; [49][50][51][52][53][54][55] however, gestational diabetes mellitus, antepartum hemorrhage, and preterm labor have been reported in chronic carriers. [56][57][58] The most significant risk of HBV infection during pregnancy is the potential for viral transmission to the fetus or neonate, 7,[59][60][61][62] which is associated with 4.5 million cases annually.…”
Section: 21mentioning
confidence: 99%
“…According to previous studies in HBV-endemic areas, infection occurs mainly in infancy and early childhood, with mother-tochild transmission (MTCT), also called vertical transmission, accounting for more than 90% of chronic infection in newborns and up to 50% in children less than 3 years old [2]. In China, the rate of HBV infection among women of childbearing age is still high (7.18%) [3] and MTCT may occur prenatally, during delivery, or in the early postpartum period.…”
Section: Introductionmentioning
confidence: 99%